Block strength training based on age-related functional consequences in older women - Emilio Jofré-Saldía; Raúl Ricardo Festa; Álvaro Villalobos-Gorigoitía; Carlos Jorquera-Aguilera; Álvaro Huerta Ojeda; Jorge Cancino-López; Gemma María Gea-García (PLoS ONE, 2025)
Strength training is a form of healthy ageing in older women. Although recommendations currently exist, some are very broad or fail to cover the needs of aging. Therefore, the purpose of this study was to analyze the effects of blocks strength training based on age-related functional consequences on functional performance in older adult women. 82 community-dwelling older women (70.17 ± 6.04 y) were randomly assigned to either experimental (n = 40) or control (n = 42) group. Experimental group performed a Block Strength Training (BST) program based on strength, power, and muscular endurance, and different level of effort for 9 weeks, and control maintained daily routine with physical activity recommendations. Functional performance was assessed using absolute handgrip strength [AHS], timed up and go [TUG], two-minutes step test [2MST], five times stand-to-sit test [5-SST], 6-m walking speed test [6-WS] pre-post intervention. Statistical analyses were performed using two-way ANOVA (Time*Group) and effect size (partial eta-squared, ŋP2) with a significance level of p < 0.05. BST improved functional performance in the protocols of AHS (21.51 vs. 23.07-kg; + 7%), TUG (8.22 vs. 7.29-sec; + 11%), 2MST (78.76 vs. 97.18-steps; + 23%), 5-SST (12.68 vs. 9.43-sec; + 26%), and 6-WS (1.16 vs. 1.36- m·s-1; + 17%) compared to control (19.31 vs. 19.66-kg; 8.94 vs. 9.26-sec; 62.68 vs. 63.73-steps; 13.99 vs. 14.25-sec; 1.06 vs. 1.06-m·s-1, respectively) in a Time*Group interaction effect (p < 0.01; ŋP2 > 0.11). This BST is effective in improving overall functional performance and thus reducing the risk of physical frailty in community-dwelling older women. These findings strengthen the approach to exercise programming over recommendations, moving toward effective precision dosing for older adults.